Judaism and Imaginary Cinema: (Jewish Iconoclasm and Vanguardist Textual Cinema) - Miguel, Alcebiades Diniz (2020)
Iconoclasm, altogether, tends to be uncritically associated with Judaism as a kind of exclusion due to prejudice or due to excessively strict observance of religious dogma. Such an association, which emerged in the Middle Ages – which fueled vast anti-Jewish literature, focused on converting Jews to Christianity – underlies a view of the Jew almost as an enemy of the visual arts, from the perspective of the spectator and the observer. But such a perspective is, of course, wrong; for iconoclasm in Judaism had many other functions and a theoretical complexity of its own. And this complexity, in a way, survived and persisted in full modernity – as we will see in the case of the avant-garde group Infra-noir, mostly Jewish, in its relations with the aesthetic and cinematographic image.